Using GPS-Based Learning Media to Improve Understanding of Map Concepts in Geography Lessons in the Independent Curriculum in Middle Schools in Aceh Province - Muliana; Aziz, Abdul; Fathimah (International Journal Education and Computer Studies (IJECS), 2024)
The concept of maps in geography reflects the desire of humanity to find out about the earth in space, orientation, physically and symbolically. As much as you try to innovate in teaching, the ability to connect theory with real world experiences students are often a struggle. Research and Development (R&D) In this study using Borg and Gall models to produce GPS -based learning media for students' understanding of the map concept. 35 students in the eighth grade, we have observed at SMP 2 Idi Timur, East Aceh facing clear challenges through map induction using traditional methods. The media produced include interactive maps, coordinate reading exercises, and activities to find real world places that make concrete geographical theory. Expert validation scores have above 90 (very valid categories), while student assessment increases (30-35%) from pretest results to post-test. GPS -based media does not only work cognitively; It works experimentally to provide significant learning, a good type of student finds their daily lives. This strategy harmonized theory with practice in the context of the independent curriculum framework, with students as active translators from geographical information instead of passive consumers. This study formulated a model where programming is not only a technical tool but also a link that connects the digital world with spatial structured reality, which ultimately contributes to sustainable development from the geographical literacy of high school students.